A density functional theory study of Na(H2O)n: An example of the impact of self-interaction corrections Guest editors: Andrey V. Solov'yov, Nigel Mason, Paulo Limão-Vieira, Malgorzata Smialek-Telega - Dinh, Phuong Mai; Gao, Cong Zhang; Klüpfel, Peter; Reinhard, Paul-Gerhard; Suraud, Eric; Vincendon, Marc; Wang, Jing; Zhang, Feng Shou (European Physical Journal D, 2014)
We present a detailed analysis of ground state and optical response properties of small metal water complexes. Such complexes represent prototypical systems for analysing chromophore effects in relation to irradiation in a biological environment. The mixing of a metal atom with organic ones leads to the coexistence of covalent and metallic bondings which requires an elaborate treatment of the self interaction correction (SIC) within density functional theory (DFT). This is a particularly key issue in the context of time dependent DFT which represents the natural tool of investigation of irradiation scenarios in such systems. We show that these complexes require a highly elaborate treatment of the SIC which can be attributed to the mixing of bonding types.
CRIS-Team Scopus Importer:2023-07-24